Influence of the method of postactivation stimulation on the performance of ski jumping from springboards of various capacities by highly qualified athletes - Kryuchkov, A. S.; Avvakumova, I. A.; Fendel, T. V.; Zubkov D. A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to evaluate the impact of exercises performed by highly qualified female athletes within the framework of the post-activation stimulation method on the performance of ski jumping from springboards of various powers.